NEED OF REVIVAL OF LACQUERED BANGLE INDUSTRY IN HYDERABAD - Babu, T.D. (Ushus Journal of Business Management, 2003)
Hyderabad has 400 years history and is well known for its heritage and culture. The city is the birth place of the lacquered bangles studded with beautiful and colourful stones made of glass pieces. The industry, unfOrtunately, still is managed by conventional families in an unprofessional way though it has lot of potential in the export market. This article discusses various causes for the lagging behind position of the industry and explores the strategic ways for its revival and development.